De novo assembly and single-molecule study of kinetochore-microtubule interactions - Larson, Joshua D.; Worst, Lillian R.; Asbury, Charles L. (Frontiers in Cell and Developmental Biology, 2026)
Kinetochores are essential molecular machines composed of dozens of protein subcomplexes that assemble onto specialized centromeric nucleosomes during every cell cycle prior to mitosis. During mitosis, the assembled kinetochores are responsible for maintaining load-bearing attachments to dynamic spindle microtubules, and for harnessing the forces generated by attached microtubules to organize and separate sister chromatids. Recent work shows that kinetochores can be reconstituted by assembling them in vitro onto centromeric DNAs in yeast whole cell lysates. By tethering individual centromeric DNAs to the surface of a coverslip, the assembly process and the microtubule-attachment activity of the assembled kinetochores can be studied at the single-molecule level. Kinetochores reconstituted in this manner are able to capture taxol-stabilized microtubules, with a strong intrinsic preference specifically for capturing microtubule plus ends. Super-resolution tracking further shows that the architecture of the assembled kinetochores changes in a microtubule polarity-dependent manner under external load. We anticipate that extensions of these approaches will uncover the molecular basis of the kinetochore’s plus end-preference and, ultimately, will reveal how tension affects the arrangement of core subcomplexes and transient regulatory factors. Here we detail how to study individual kinetochores assembled from yeast whole cell lysate using single-molecule total internal reflection fluorescence microscopy.